2019
DOI: 10.1080/0886022x.2019.1590211
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of oral rehydration solution III in exertional heatstroke rats

Abstract: Aim: Exertional heastroke (EHS) can lead to acute kidney injury. Oral rehydration solution III (ORS III), recommended by WHO in 2004, is used to rehydrate children with gastroenteritis. This study aimed to characterize the renoprotective effect of ORS III in EHS rats. Methods: Rats were randomly divided into Group Control, Group EHS, Group EHS þ Water, and Group EHS þ ORS. Thirty minutes before the experiment, ORS III was orally administrated to Group EHS þ ORS, Water was given to Group EHS þ Water. Rats from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Recent findings support that the aetiology of kidney injury during heatstroke also includes injury to the renal tubules (Lin & Zhang, 2019). This study additionally identified serum neutrophil gelatinase-associated lipocalin (NGAL) as a potential early biomarker of kidney injury secondary to EHS, such that elevations in serum NGAL were almost 10 times higher post-EHS compared to a non-heated control group (Lin & Zhang, 2019). Such observations are consistent with findings in humans undertaking exercise in the heat (Schlader et al, 2017).…”
Section: Kidneyssupporting
confidence: 85%
See 1 more Smart Citation
“…Recent findings support that the aetiology of kidney injury during heatstroke also includes injury to the renal tubules (Lin & Zhang, 2019). This study additionally identified serum neutrophil gelatinase-associated lipocalin (NGAL) as a potential early biomarker of kidney injury secondary to EHS, such that elevations in serum NGAL were almost 10 times higher post-EHS compared to a non-heated control group (Lin & Zhang, 2019). Such observations are consistent with findings in humans undertaking exercise in the heat (Schlader et al, 2017).…”
Section: Kidneyssupporting
confidence: 85%
“…This likely occurs secondarily to the heatstroke-induced systemic inflammation and coagulation activation that catalyse haemorrhagic and thrombotic events within the kidneys (and other organs), similar to sepsis (Ma et al, 2019). Recent findings support that the aetiology of kidney injury during heatstroke also includes injury to the renal tubules (Lin & Zhang, 2019). This study additionally identified serum neutrophil gelatinase-associated lipocalin (NGAL) as a potential early biomarker of kidney injury secondary to EHS, such that elevations in serum NGAL were almost 10 times higher post-EHS compared to a non-heated control group (Lin & Zhang, 2019).…”
Section: Kidneysmentioning
confidence: 93%
“…To date, no published animal research has attempted to evaluate the role of GI MT on EHS pathophysiology. Inconsistent with EHS GI paradigm, recent data demonstrate the pattern of cytokine response during EHS to be largely inconsistent to those displayed following GI microbial PAMP recognition (e.g., minimal TNF-α/IL-1β response; [60]. With this is mind, it is plausible that cytokine production initiated in response multiple organ injury (e.g., skeletal muscle; [61]) performs a greater role in EHS pathophysiology than previously proposed [37,47].…”
Section: The Gi Exertional Heat Stroke Paradigmmentioning
confidence: 98%
“…Similarly, direct intravenous endotoxin injection prior to sub-lethal CHS in rodents (peak T core =~42-43 • C) unexpectedly led to fatalities in 40% of animals (versus 0% in controls; [57]), or best-case increased symptoms of multiple-organ injury [58]. At present, only one study has assessed the role of GI barrier integrity utilising a relevant EHS model, whereby rats run to thermal collapse in the heat (T core = 40.5-42.5 • C) displayed significant histopathological damage to all GI segments [59,60], together with a significant pro-inflammatory response [61]. However, in comparison to CHS models with a similar clinical endpoint (peak T core =~42-42.5 • C), the magnitude of GI barrier integrity loss was lower following EHS, though this finding is potentially attributable to ã 50% lower thermal area [60].…”
Section: The Gi Exertional Heat Stroke Paradigmmentioning
confidence: 99%
See 1 more Smart Citation